Bonding Durability Evaluation of Polymer-Modified Emulsified Asphalt Microsurfacing - Hao Fu; Qian Chen; Xiaolong Sun; Wenwu Zhang; Shanshan Wang (Advances in Materials Science and Engineering)
At present, there are few research studies on the durability of microsurfacing. To further improve the service quality and durability of microsurfacing, five kinds of polymer-modified emulsified asphalt were used to prepare microsurfacing mixture. Based on the mixing time, wet track abrasion test, and load wheel test, the composition rationality of the microsurfacing mixture was verified. The influence of different polymer-modified emulsified asphalt on the water damage resistance, deformation resistance, and skid resistance of the microsurfacing was analyzed. The destructive effects of complex climatic conditions on the microsurfacing were simulated by means of damp heat aging, freeze-thaw cycle, and xenon lamp light aging treatment. Taking the wear resistance and pull-off properties after aging treatment and the change rate of various properties before and after treatment as evaluation indexes, the bonding durability of the microsurfacing was comprehensively evaluated by the ideal point method of entropy weight. The results show that the water damage resistance, abrasion resistance, and deformation resistance of the microsurfacing have a high correlation with the mechanical strength and adhesion performance of the modified emulsified asphalt binder. Xenon lamp aging has a significant impact on the bonding performance of the microsurfacing. Waterborne epoxy resin can effectively improve the bonding performance and bonding durability of the microsurfacing. Waterborne polyurethane can improve the freeze-thaw resistance and xenon lamp aging resistance of the microsurfacing.